The association of living donor source with patient and graft survival among kidney transplant recipients in the ERA‐EDTA Registry – a retrospective study. (26th October 2020) - Abd ElHafeez, Samar; Noordzij, Marlies; Kramer, Anneke; Bell, Samira; Savoye, Emilie; Abad Diez, José Maria; Lundgren, Torbjörn; Reisæter, Anna Varberg; Kerschbaum, Julia; Santiuste de Pablos, Carmen; Ortiz, Fernanda; Collart, Frederic; et al.
Summary: In this study we aimed to compare patient and graft survival of kidney transplant recipients who received a kidney from a living‐related donor (LRD) or living‐unrelated donor (LUD). Adult patients in the ERA‐EDTA Registry who received their first kidney transplant in 1998–2017 were included. Ten‐year patient and graft survival were compared between LRD and LUD transplants using Cox regression analysis. In total, 14 370 patients received a kidney from a living donor. Of those, 9212 (64.1%) grafts were from a LRD, 5063 (35.2%) from a LUD and for 95 (0.7%), the donor type was unknown. Unadjusted five‐year risks of death and graft failure (including death as event) were lower for LRD transplants than for LUD grafts: 4.2% (95% confidence interval [CI]: 3.7–4.6) and 10.8% (95% CI: 10.1–11.5) versus 6.5% (95% CI: 5.7–7.4) and 12.2% (95% CI: 11.2–13.3), respectively. However, after adjusting for potential confounders, associations disappeared with hazard ratios of 0.99 (95% CI: 0.87–1.13) for patient survival and 1.03 (95% CI: 0.94–1.14) for graft survival. Unadjusted risk of death‐censored graft failure was similar, but after adjustment, it was higher for LUD transplants (1.19; 95% CI: 1.04–1.35). In conclusion, patient and graft survival of LRD and LUD kidney transplant recipients was similar, whereas death‐censored graft failure was higher in LUD. These findings confirm the importance of both living kidney donor types.